2014
DOI: 10.1093/annhyg/meu091
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Workplace Assessments of Rivet Bucking Bar Vibration Emissions

Abstract: Sheet metal workers operating rivet bucking bars are at risk of developing hand and wrist musculoskeletal disorders associated with exposures to hand-transmitted vibrations and forceful exertions required to operate these hand tools. New bucking bar technologies have been introduced in efforts to reduce workplace vibration exposures to these workers. However, the efficacy of these new bucking bar designs has not been well documented. While there are standardized laboratory-based methodologies for assessing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Although the data from the simulated test may not have much value for risk assessment, it demonstrates that the club head vibration can be reduced by adding mass and damping. This concept is similar to that used for reducing the handheld bucking bar vibration in a riveting process (McDowell et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Although the data from the simulated test may not have much value for risk assessment, it demonstrates that the club head vibration can be reduced by adding mass and damping. This concept is similar to that used for reducing the handheld bucking bar vibration in a riveting process (McDowell et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The steel and tungsten rivet bucking bars in Tables 4 and 5 were assessed in the field tests on airplane frames in our reported study [36]. Rivet hammer H in Table 4 was used to set the rivets with the bars.…”
Section: Discussionmentioning
confidence: 99%
“…If such alternative weightings are used for assessing the glove effectiveness, the vibration components at frequencies above 500 Hz cannot be ignored in many cases. For example, significant vibration components can be observed in the range of 500 to 1,250 Hz on the percussive tools, bucking bars, and golf club heads [35,36]. If the unit weighting is used, the gloves will appear to be more effective than their percent reductions shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is no standardized method for comparing rivet bucking bars in terms of their vibration exposures. To that end, a recent NIOSH study included the development of a laboratory-based method for evaluating bucking bar vibrations (McDowell et al, 2015). That study found that the NIOSH test method shows promise for identifying rivet bucking bar designs that may reduce workplace HTV exposures to sheet metal workers, but the bucking bar test method is in need of some refinements.…”
Section: Introductionmentioning
confidence: 99%